Unintended consequences of infection prevention and control measures during COVID-19 pandemic - Wee, Liang En Ian (Am J Infect Control, 2021)
BACKGROUND: In the current COVID-19 pandemic, aggressive Infection Prevention and Control (IPC) measures have been adopted to prevent health care-associated transmission of COVID-19. We evaluated the impact of a multimodal IPC strategy originally designed for the containment of COVID-19 on the rates of other hospital-acquired-infections (HAIs). METHODOLOGY: From February-August 2020, a multimodal IPC strategy was implemented across a large health care campus in Singapore, comprising improved segregation of patients with respiratory symptoms, universal masking and heightened adherence to Standard Precautions. The following rates of HAI were compared pre- and postpandemic: health care-associated respiratory-viral-infection (HA-RVI), methicillin-resistant Staphylococcus aureus, and CP-CRE acquisition rates, health care-facility-associated C difficile infections and device-associated HAIs. RESULTS: Enhanced IPC measures introduced to contain COVID-19 had the unintended positive consequence of containing HA-RVI. The cumulative incidence of HA-RVI decreased from 9.69 cases per 10,000 patient-days to 0.83 cases per 10,000 patient-days (incidence-rate-ratio = 0.08; 95% confidence interval [CI] = 0.05-0.13, P< .05). Hospital-wide MRSA acquisition rates declined significantly during the pandemic (incidence-rate-ratio = 0.54, 95% CI = 0.46-0.64, P< .05), together with central-line-associated-bloodstream infection rates (incidence-rate-ratio = 0.24, 95% CI = 0.07-0.57, P< .05); likely due to increased compliance with Standard Precautions. Despite the disruption caused by the pandemic, there was no increase in CP-CRE acquisition, and rates of other HAIs remained stable. CONCLUSIONS: Multimodal IPC strategies can be implemented at scale to successfully mitigate health care-associated transmission of RVIs. Good adherence to personal-protective-equipment and hand hygiene kept other HAI rates stable even during an ongoing pandemic where respiratory infections were prioritized for interventions.